2021
DOI: 10.18502/ijaai.v20i2.6057
|View full text |Cite
|
Sign up to set email alerts
|

Production of SARS-CoV-2 Antibodies and Emergence of the Clinical Symptoms of COVID-19

Abstract: Coronavirus disease 2019 (COVID-19) is a worldwide public health problem that has attracted much attention due to its clinical findings. Measurement of IgG and IgM antibodies is of great importance for researchers and it will help to develop a new diagnostic and therapeutic method in clinical care. In this cross-sectional study, we aim to measure the IgG and IgM antibody levels in 401 suspected COVID-19 volunteers. We also measure the time duration for the appearance of IgG and IgM antibodies from the onset of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…All results presented so far refer to the detection of IgG antibodies that usually start to form a few weeks after an infection. Even before that, IgM antibodies are formed so that a detection of both IgM and IgG can give important information about the course of an infection, even though it has been shown that for COVID-19, IgM production occurs relatively late and therefore not notably before IgG can be detected already. , But still, information about the presence or absence of IgM antibodies is valuable in assessing how long ago the infection has occurred as the IgM titers plummet faster than the IgG titers.…”
Section: Resultsmentioning
confidence: 99%
“…All results presented so far refer to the detection of IgG antibodies that usually start to form a few weeks after an infection. Even before that, IgM antibodies are formed so that a detection of both IgM and IgG can give important information about the course of an infection, even though it has been shown that for COVID-19, IgM production occurs relatively late and therefore not notably before IgG can be detected already. , But still, information about the presence or absence of IgM antibodies is valuable in assessing how long ago the infection has occurred as the IgM titers plummet faster than the IgG titers.…”
Section: Resultsmentioning
confidence: 99%
“…Memory plasma cells go on to continuously secrete antibodies which allow the immune system to maintain a stable humoral immunological memory over long periods. In this way, multiple studies are investigating seroprevalence within different populations, for example, in patients with cancer [14] and within different environmental contexts [15,16]. These studies are mainly focused on IgG [17] and IgM patterns for each cohort or in relation to COVID-19 symptoms and severity [18,19].…”
Section: Introductionmentioning
confidence: 99%